Combination of nuclear magnetic resonance spectroscopy and nonlinear methods to analyze the copolymerization of phosphonic acid derivatives - Heinze, Marcus; Starke, Sandra; Haendler, Marcel; Komber, Hartmut; Drache, Marco; Moszner, Norbert; Voit, Brigitte; Pospiech, Doris (Journal of Applied Polymer Science, 2019)
We demonstrate in this study that the combination of modern inline monitoring methods [here: inline nuclear magnetic resonance (NMR)] with simulations gains more exact and profound kinetic results than previously used methods like linearization without that combination. The 1H-NMR spectroscopic data (more than 100 data points) are used to construct the copolymerization diagram. The reactivity ratios are obtained applying the van Herks nonlinear least square method. The examination of the radical copolymerization of 2-hydroxyethyl methacrylate (HEMA) with (2-[2-(ethoxycarbonyl)prop-2-en-1-yl]oxyethyl) phosphonic acid (ECPPA) as important adhesive monomer used in dentistry yields reactivity ratios of rHEMA = 1.83; rECPPA = 0.42. The copolymerization diagram reflects nonideal, non-azeotropic copolymerization. The sequence distribution of the obtained by Monte Carlo simulation indicates the generation of statistical copolymers. As an important finding, it is demonstrated that the repeating units responsible for etching and adhesion are arranged over the whole polymer chain, which is necessary to achieve proper functionality. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48256.
CRIS-Team Scopus Importer:2022-04-14
Keywords: (2-[2-(ethoxycarbonyl)prop-2-en-1-yl]oxyethyl) phosphonic acid; 2-hydroxymethyl methacrylate; inline; radical copolymerization; reactivity ratio; sequence distribution analysis